A Study on Zermelo Navigation Problem - PoojaSwaroopSaxena (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, mathematical formulation of navigation problem using Riemannian &Finsler geometry is discussed.Special situations with complete mathematical solutions of the problemare mentioned, namelyFinsler space with constant flag curvature and other. Modeling of the aircraft motion is introduced.